Bupropion for depression in schizophrenia - Englisch, Susanne Angelika; Inta, Dragos; Eßer, Andrea; Zink, Mathias (Clinical neuropharmacology, 2010)
Objectives: The catecholaminergic theory of depression assumes dysfunctional neurotransmission of dopamine and norepinephrine. Therefore, the antidepressant bupropion, a dual dopamine and norepinephrine reuptake inhibitor, might be a valuable treatment option also in schizophrenic patients with major depressive episodes. However, reports on induced psychotic symptoms in depressed patients questioned its use in patients with psychotic spectrum lifetime diagnoses. Here, we report on treatment experiences with bupropion in patients with schizophrenia with respect to antidepressive efficacy, safety, and tolerability. - Methods: We report on a consecutive series of depressed patients with psychotic spectrum lifetime diagnoses who received bupropion extended release for a period of 6 weeks in addition to stable doses of antipsychotic agents (N = 5). The psychometric scales Positive and Negative Syndrome Scale, Scale for the Assessment of Negative Symptoms, Calgary Depression Scale for Schizophrenia, Hamilton Depression Scale, and Extrapyramidal Symptoms Scale were applied. - Results: All patients experienced significant improvements of their major depressive episodes. Psychotic positive symptoms remained stably absent, whereas both negative symptoms and global psychopathology considerably improved. The treatment was generally well tolerated; however, subtle electroencephalographic deteriorations were observed. - Conclusions: This case series suggests safe and effective antidepressive treatment with bupropion in patients with schizophrenic disorders, if stable antipsychotic medication and electroencephalographic-monitoring are provided. Further randomized studies involving a control group are necessary.
Gesehen am 25.05.2023